PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY TERHADAP RETURN: ANALISIS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2014-2018 - Tyas Nur’Aini; Lailatus Sa’adah; Ita Rahmawati (Jurusan Akuntansi, Universitas Bangka Belitung, 2020)
This study aims to analyse the effect of the current ratio, debt to equity ratio, return on equity to return on Food and Beverage companies listed on the Indonesia Stock Exchange in 2014-2018, both partially and simultaneously. The population in this study are all Food and Beverage companies listed on the Indonesia Stock Exchange in 2014-2018, amounting to 26 companies. The sampling technique in this study used a non probability sampling method by purposive sampling and the samples taken were 5 companies. The technique of collecting research data uses documentation obtained from the Indonesia Stock Exchange website and its data analysis techniques use panel data regression analysis, classic assumption test and hypothesis test. Based on the t test that has been done shows that partially the current ratio (CR) does not significantly influence the return on Food and Beverage companies listed on the Indonesia Stock Exchange in 2014-2018, debt to equity ratio (DER) does not significantly influence the return on Food and Beverage companies listed on the Indonesia Stock Exchange in 2014-2018, return on equity (ROE) has a significant effect on returns on Food and Beverage companies listed on the Indonesia Stock Exchange in 2014-2018. based on the F test it can be concluded that the current ratio, debt to equity ratio and return on equity together have no effect on returns on Food and Beverage companies listed on the Indonesia Stock Exchage in 2014-2018.